Stop Bullying Wujudkan Generasi Berakhlak di SMK Tanah Luas Kabupaten Aceh Utara - Maryam, Maryam; Aiyub, Aiyub; Muryali, Muryali; Yani, Ahmad; Nazaruddin, Nazaruddin (Universitas Malikussaleh, 2025)
Adolescence is a crucial transition phase in the formation of a person's character and mentality, where adolescents begin to face various challenges, both in physical, emotional, social, and psychological aspects. One of the problems that often arise at this stage is bullying, which can interfere with the mental and social development of adolescents. The phenomenon of bullying, both in the school environment and in the community, needs serious attention to create a safe and healthy environment for adolescents. This research aims to educate adolescents about the importance of building strong characters and avoiding bullying through an educational program conducted at SMK 1 Tanah Luas North Aceh. The methods used in this activity include the delivery of educational materials, discussions, and ice breaking to create a fun and interactive learning atmosphere. The results of this activity show that the education carried out is effective in increasing students' understanding of bullying, the importance of noble morals, and mutual respect for others. Through a fun and participatory approach, students can better understand the importance of good character formation as a preventive measure against bullying behavior. It is hoped that this activity can make a positive contribution to creating a generation with noble character, avoiding bullying, and having a strong character in facing various challenges in life.